Directed search for compounds that affect the excretory function of rat kidneys, among new cycloalkylcarbonyl thioureas and thiosemicarbazides derivatives - Kholodniak, O. V.; Sokolova, K. V.; Pidpletnya, O. A.; Холодняк, Олена Валеріївна; Соколова, К. В.; Коваленко, Сергій Іванович; Підплетня, О. А.; Холодняк, А. В.; Соколова, К. В.; Коваленко, С. И.; Пидплетня, А. А.; Kovalenko, S. I. (My University, 2020)
. Prolonged usage of diuretics, especially in large doses, the number and severity of side effects (water-electrolyte and metabolic disorders), as well as the relatively limited range of existing diuretics dictate the need to find new compounds that would have diuretic effects, simple production technology and would be safer. The aim of the study – directed search for diuretics among unknown disubstituted thioureas and thiosemicarbazides using the molecular docking methodology as the way to explain the probable mechanism of action. Research Methods. The structures of the target compounds have been proposed using drug-design approaches, namely the introduction of structural fragments into thioureas and thiosemicarbazides, which are characteristic of known diuretics. The synthesis of substituted cycloalkylcarbonylthioureas or thiosemicarbazides was carried out by a single-reactor method using cycloalkylcarbonyl chlorides, ammonium isothiocyanate and substituted anilines or carboxylic acid hydrazides. The structure of the synthesized compounds was proved by IR, 1 H NMR spectroscopy, chromato-mass spectrometry and elemental analysis. Probable molecular mechanisms of activity were predicted due to molecular docking. Directed search for compounds that affect the excretory function of the kidneys of rats was conducted by the conventional method of E.B. Berkhin with water load. Results and Discussion. It has been found that the single-reaction of cycloalkylcarbonyl chlorides with an equimolecular amount of ammonium isothiocyanate and substituted anilines or carboxylic acid hydrazides resulted in formation of substituted cycloalkylcarbonylthioureas or thiosemicarbazides. The structure of the synthesized compounds was discussed using IR, 1 H NMR and chromato-mass spectra. Studies of the effect of the synthesized compounds on the excretory function of rats kidneys under water load have revealed several compounds that exceed the diuretic effect of “Furosemide” and compete with “Hydrochlorothiazide”. Molecular docking results have shown that the test compounds demonstrated a high affinity for carbonic anhydrase II and similar binding sites to reference drugs. This indicates their probable mechanism of action. Conclusion. The developed and implemented strategy for searching of diuretics among cycloalkylcarbonyl thioureas and thiosemicarbazides derivatives has allowed to identify an effective compound (3.2), which is close to the reference drug “Hydrochlorothiazide” in terms of diuretic effect. Importantly, according to the results of molecular docking, the synthesized compounds as well as the reference drugs have a similar mechanism of action (carbonic anhydrase II inhibitors). It is likely, that the expressed diuretic effect of several compounds is related to the ability of substituted thioureas to form coordination bonds with the zinc cation in the active site of CA II. The obtained results substantiate the further purposeful search for potential diuretics among this class of compounds. Тривале застосування діуретиків, особливо у великих дозах, численність і тяжкість побічних ефектів (водно-електролітні й метаболічні порушення), а також відносно обмежена номенклатура існуючих діуретичних засобів диктують необхідність пошуку нових сполук, які б проявляли діуретичну дію, мали нескладну технологію виробництва та були більш безпечними. Мета дослідження – здійснити спрямований пошук діуретиків серед невідомих дизаміщених тіосечовин і тіосемікарбазидів з використанням методології молекулярного докінгу для пояснення імовірного механізму дії. Методи дослідження. Структури цільових сполук запропоновано із застосуванням підходів “drugdesign”, а саме введенням до тіосечовин і тіосемікарбазидів структурних фрагментів, характерних для відомих діуретиків. Заміщені циклоалкілкарбонілтіосечовини чи тіосемікарбазиди синтезовано однореакторним методом з використанням циклоалкілкарбонілхлоридів, амонію ізотіоціанату та заміщених анілінів або гідразидів карбонових кислот. Будову синтезованих сполук доведено методами ІЧ-, 1 Н ЯМР-спектроскопії, хроматомас-спектрометрії та елементним аналізом. Спрямований пошук сполук, що впливають на видільну функцію нирок щурів, здійснено за загальноприйнятим методом Є. Б. Бєрхіна з водним навантаженням. Імовірний молекулярний механізм дії передбачено завдяки молекулярному докінгу. Результати й обговорення. Однореакторна реакція циклоалкілкарбонілхлоридів з еквімолекулярною кількістю амонію ізотіоціанату та заміщених анілінів або гідразидів карбонових кислот приводить до заміщених циклоалкілкарбонілтіосечовин чи тіосемікарбазидів. Обговорено будову синтезованих сполук з використанням даних ІЧ-, 1 Н ЯМР- і хроматомас-спектрів. Дослідження впливу синтезованих сполук на видільну функцію нирок щурів при водному навантаженні дозволили виявити ряд сполук, які за діуретичною дією перевищують фуросемід та конкурують з гідрохлортіазидом. Результати молекулярного докінгу показали, що досліджувані сполуки проявляли високу спорідненість до карбоангідрази II і мали подібні сайти зв’язування з референс-препаратами. Зазначене вказує на ймовірний їх механізм дії. Висновки. Розроблена та реалізована стратегія пошуку діуретиків серед заміщених циклоалкілкарбонілтіосечовин і тіосемікарбазидів дозволила виявити ефективну сполуку (3.2), яка за силою сечогінного ефекту наближається до референс-препарату “Гідрохлортіазид”. Важливо, що, згідно з результатами молекулярного докінгу, синтезовані сполуки, як і референс-препарати, мають подібний механізм дії (інгібітори карбоангідрази II). Імовірно, виражений діуретичний ефект досліджуваних сполук пов’язаний зі здатністю заміщених тіосечовин утворювати координаційні зв’язки з катіоном цинку в активній ділянці СА II. Отримані результати обґрунтовують подальший цілеспрямований пошук потенційних діуретиків серед цього класу сполук. Длительное применение диуретиков, особенно в больших дозах, численность и тяжесть побочных эффектов (водно-электролитные и метаболические нарушения), а также относительно ограниченная номенклатура существующих диуретических средств диктуют необходимость поиска новых соединений, которые бы проявляли диуретическое действие, имели несложную технологию производства и были более безопасными. Цель исследования – осуществить направленный поиск диуретиков среди неизвестных дизамещенных тиомочевин и тиосемикарбазидов с использованием методологии молекулярного докинга для объяснения возможного механизма действия. Методы исследования. Структуры целевых соединений предложены с применением подходов “drugdesign”, а именно введением в тиомочевины и тиосемикарбазиды структурных фрагментов, характерных для известных диуретиков. Замещенные циклоалкилкарбонилтиомочевины или тиосемикарбазиды синтезированы однореакторным методом с использованием циклоалкилкарбонилхлоридов, аммония изотиоцианата и замещенных анилинов или гидразидов карбоновых кислот. Строение синтезированных соединений доказано методами ИК-, 1 Н ЯМР-спектроскопии, хромато-масс-спектрометрии и элементным анализом. Направленный поиск соединений, влияющих на выделительную функцию почек крыс, осуществлен по общепринятому методу Е. Б. Берхина с водной нагрузкой. Вероятный молекулярный механизм действия предусмотрен благодаря молекулярному докингу. Результаты и обсуждение. Однореакторная реакция циклоалкилкарбонилхлоридов с эквимолекулярным количеством аммония изотиоцианата и замещенных анилинов или гидразидов карбоновых кислот приводит к замещенным циклоалкилкарбонилтиомочевинам или тиосемикарбазидам. Обсуждено строение синтезированных соединений с использованием данных ИК-, 1 Н ЯМР- и хроматомасc-спектров. Исследования влияния синтезированных соединений на выделительную функцию почек крыс при водной нагрузке позволили выявить ряд соединений, которые по диуретическому действию превышают фуросемид и конкурируют с гидрохлортиазидом. Результаты молекулярного докинга показали, что исследуемые соединения проявляли высокое сродство к карбоангидразе II и имели подобные сайты связывания с референс-препаратами. Отмеченное указывает на вероятный их механизм действия. Выводы. Разработанная и реализованная стратегия поиска диуретиков среди замещенных циклоалкилкарбонилтиомочевин и тиосемикарбазидов позволила выявить эффективное соединение (3.2), которое по силе мочегонного эффекта приближается к референс-препарату “Гидрохлортиазид”. Важно то, что, согласно результатам молекулярного докинга, синтезированные соединения, как и референс-препараты, имеют сходный механизм действия (ингибиторы карбоангидразы II). Вероятно, выраженный диуретический эффект исследуемых соединений связан со способностью замещенных тиомочевин образовывать координационные связи с катионом цинка в активном участке СА II. Полученные результаты обосновывают дальнейший целенаправленный поиск потенциальных диуретиков среди этого класса соединений.
Спрямований пошук сполук, що впливають на видільну функцію нирок щурів, серед нових похідних циклоалкілкарбонілтіосечовин і тіосемікарбазидів
Направленный поиск соединений, влияющих на выделительную функцию почек крыс, среди новых производных циклоалкилкарбонилтиомочевин и тиосемикарбазидов
Keywords: synthesis; cycloalkylcarbonyl thioureas and thiosemicarbazides; spectral data; molecular docking; carbonic anhydrase II; diuretic activity; синтез; циклоалкілкарбонілтіосечовини; тіосемікарбазиди; спектральні дані; молекулярний докінг; карбоангідраза II; діуретична дія; синтез; циклоалкилкарбонилтиомочевины; тиосемикарбазиды; спектральные данные; молекулярный докинг; карбоангидраза II; диуретическое действие